Acupuncture combined with repetitive transcranial magnetic stimulation for the treatment of post-stroke depression: a systematic evaluation and meta-analysis based on a randomised controlled trial - Xiao, Keyuan; Li, Xiang; Hu, Wenqing; Li, Xinghua (Frontiers in Neurology, 2024)
Objective: The objective of this study was to systematically evaluate the effectiveness of combining acupuncture with repetitive transcranial magnetic stimulation (rTMS) for the treatment of post-stroke depression. Methods: We conducted a thorough search in eight major domestic and international databases, including China Knowledge Network (CKN), from their inception until December 2023. Randomized controlled trials that investigated the use of acupuncture combined with rTMS for post-stroke depression were included. The screening process followed predetermined inclusion and exclusion criteria, and the quality of the included studies was assessed using the evaluation criteria outlined in the Cochrane Handbook 5.1. Meta-analysis was performed using RevMan 5.4. Results: A total of 11 studies, comprising 924 patients, were included in the analysis. The meta-analysis results demonstrated that acupuncture combined with rTMS treatment significantly increased the clinical effective rate (RR=1.19, 95% CI: 1.12-1.27, P<0.000 01) and decreased the scores on the Hamilton Depression Scale (HAMD) (MD=-3.45, 95%